Screening for prostate cancer: an update. - Shariat, S; Scardino, P; Lilja, H (2008)
The introduction of total prostate-specific antigen (tPSA) testing in serum has revolutionized the detection and management of men with prostate cancer. This review will highlight some of the exciting new developments in the field of prostate cancer screening in general and from our SPORE research program at Memorial-Sloan Kettering Cancer Center. First, it is important to understand that the inherent variability of tPSA levels affects the interpretation of any single results. Total variation in tPSA includes both analytical (i.e., pre-analytical sample handling, laboratory processing, assay performance, and standardization) and biological variation (i.e., metabolism, renal elimination, medication, physical and sexual activity, size and integrity of the prostate). Second, recent evidence demonstrates that no single tPSA cut-off separates men at high risk for prostate cancer from men at low risk or men with "significant" (high grade, high volume) cancer from those with low grade, indolent cancer. Taken together with a man's age, family history, ethnicity, and digital rectal exam results, tPSA levels add to the overall estimate of the risk of cancer, allowing men to share in the decision about a biopsy. Third, men who will eventually develop prostate cancer have increased tPSA levels years or decades before the cancer is diagnosed. These tPSA levels may reflect the long duration of prostate carcinogenesis and raise the question about a causal role for tPSA in prostate cancer development and progression. Total prostate-specific antigen measurements before age 50 could help risk stratify men for intensity of prostate cancer screening. Fourth, enhancing the diagnostic accuracy of tPSA, especially its specificity, is of particular importance, since higher specificity translates into fewer biopsies in men not affected by prostate cancer. While tPSA velocity has been shown to improve the specificity of tPSA, its sensitivity is too low to avoid prostate biopsy in a patient with an elevated tPSA level. Moreover, prospective screening studies have reported that tPSA velocity does not add diagnostic value beyond tPSA level. At this time, tPSA velocity appears most useful after diagnosis and after treatment, but its value in screening and prognostication remains to be shown. Finally, while free PSA molecular isoforms and human kallikrein-related peptidase 2 (hK2) hold the promise for detection, staging, prognosis, and monitoring of prostate cancer, evidence from large prospective clinical trials remain to be reported.